Unilateral Stereotactic Posteroventral Globus Pallidus Internus Pallidotomy for Parkinson's Disease: Surgical Techniques and 2-Year Follow-Up - Chun-Po Yen; Shiao-Jing Wu; Yu-Feng Su; Aij-Lie Kwan; Sheng-Long Howng (Kaohsiung Journal of Medical Sciences, 2005)
With the advent of levodopa (L-dopa) and the recognition of its striking effect on Parkinson's disease (PD), virtually all surgical procedures for PD ceased from the mid 1960s. However, there has been a resurgence of pallidotomy and other stereotactic procedures in the last two decades as physicians realized that most PD patients eventually face medical failure after long-term treatment with L-dopa. Nine PD patients, three men and six women, with an average age of 62 years and disease duration of 13 years underwent unilateral globus pallidus internus (GPi) pallidotomy contralateral to the side with marked akinetic symptoms and drug-induced dyskinesia. All patients were evaluated using the Unified Parkinson's disease Rating Scale (UPDRS) after drug withdrawal and while taking their optimal medical regimen, preoperatively and 6, 12, and 24 months after surgery. There was significant improvement in activities of daily living and motor subscores as well as total UPDRS score in the “off” state at the 2-year follow-up, which mainly resulted from improvement in contralateral bradykinesia and rigidity. Significant improvements in contralateral akinetic symptoms and drug-induced dyskinesia were also observed in the “on” state and were sustained for at least 2 years. Ipsilateral and axial symptoms were not altered by unilateral GPi pallidotomy. The complications of surgery were generally well tolerated. One patient had a small postoperative asymptomatic hemorrhage identified by routine follow-up magnetic resonance imaging. Another two patients developed temporary sexual disinhibition and auditory hallucination, respectively, which resolved spontaneously 2 weeks after surgery. The effect of pallidotomy for alleviation of akinetic parkinsonism is modest but significant, and continues to be effective for at least 2 years. Further analytical studies, especially the correlation of clinical effects and lesion locations, are important not only to provide direct feedback for surgeons to examine the technical accuracy and but also to facilitate understanding of the pathophysiology of PD.